2012
DOI: 10.4103/1119-3077.94093
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidant vitamins and the risk of oral cancer in patients seen at a tertiary institution in Nigeria

Abstract: The lower serum vitamin A, C, and E levels in oral cancer patients could be either a cause or an effect of the oral cancer. Further studies using a larger sample size and cohort studies with long-term follow-up of subjects are desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 10 publications
4
26
1
1
Order By: Relevance
“…Zheng et al (1993) also reported significant association between retinol and α-tocopherol with oral cancer risk. This finding is further corroborated by an earlier study where serum level of vitamin A (a group of organic compound including retinol) and E (a group of organic compound including tocopherol) was also found to be lower in cases as compared to controls where low serum level of these vitamins was associated with 10.9 times and 5.6 times increased risk for oral cancer (Lawal et al, 2012). Inverse association of retinol and α-tocopherol have also been reported in other cancers such as lung (Klarod et al, 2011), breast (Shim et al, 2012) and gastric cancer (Jenab et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Zheng et al (1993) also reported significant association between retinol and α-tocopherol with oral cancer risk. This finding is further corroborated by an earlier study where serum level of vitamin A (a group of organic compound including retinol) and E (a group of organic compound including tocopherol) was also found to be lower in cases as compared to controls where low serum level of these vitamins was associated with 10.9 times and 5.6 times increased risk for oral cancer (Lawal et al, 2012). Inverse association of retinol and α-tocopherol have also been reported in other cancers such as lung (Klarod et al, 2011), breast (Shim et al, 2012) and gastric cancer (Jenab et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…The synergism among vitamin E, ascorbate, and selenium inhibits DNA and RNA protein synthesis in the cells. 10 In the present study, mean serum vitamin E levels inpatients with oral potentially malignant disorders were significantly lower than that in controls, which is in agreement with a study by Gupta et al on oral submucous fibrosis. This could be attributed to the potent lipophilic action of vitamin E, which gets consumed in conditions of oxidative stress, thus lowering its levels.…”
Section: Discussionsupporting
confidence: 82%
“…The discussion in these studies was based on the fact that the increase in the incidence and mortality rates of many cancer types might be due to the loss of protective feature of uric acid in case of low serum concentration levels [21]. Bozkir et al [22], in their study comparing healthy control subjects with lung cancer patients, found that serum uric acid levels of the lung cancer patients were significantly lower.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have emphasized low serum uric acid level's association with increased cancer prevalence and high mortality rate [21][22][23]. The discussion in these studies was based on the fact that the increase in the incidence and mortality rates of many cancer types might be due to the loss of protective feature of uric acid in case of low serum concentration levels [21].…”
Section: Discussionmentioning
confidence: 99%